Need analysis of digital technology-based push up test: Instrument of arm muscle strength - Artanayasa, I Wayan; Kusuma, Ketut Chandra Adinata; Ariawan, Ketut Udy (Journal Sport Area, 2022)
The rapid development of science and technology has an impact on the development of sports, both achievement sports, educational sports, and recreational sports. The use of technology and sport science is very important for the advancement of sports achievements. One of these implementations is the stage of testing and measuring physical conditions using instruments with a low level of human error. The purpose of this study was to analyze the need for the development of a digital technology-based push up test as an instrument for arm muscle strength. This research is a survey research that uses a quantitative descriptive approach. 256 respondents with a background as a lecturer at the Faculty of Sports and Health Undiksha, as well as athletes from Buleleng Regency, Badung Regency, Bangli Regency and Denpasar City filled out a questionnaire consisting of six statements. Questionnaires are used to determine the opinion of respondents on the needs of the developed instrument. Based on the results of the survey, the majority of respondents experienced difficulties in doing push up according to the procedure, and they stated that the manual push up test was prone to human error during calculations. Thus, all respondents agree with the development of digital technology-based arm muscle strength instruments. Referring to the results of the research above, this data can be one of the basic considerations in the development of a digital technology-based push up test which is intended in the process of measuring arm muscle strength with a good level of validity.